2022
DOI: 10.1038/s41598-022-08111-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of PemIK (PemK/PemI) type II TA system from Klebsiella pneumoniae clinical strains in lytic phage infection

Abstract: Since their discovery, toxin-antitoxin (TA) systems have captivated the attention of many scientists. Recent studies have demonstrated that TA systems play a key role in phage inhibition. The aim of the present study was to investigate the role of the PemIK (PemK/PemI) type II TA system in phage inhibition by its intrinsic expression in clinical strains of Klebsiella pneumoniae carrying the lncL plasmid, which harbours the carbapenemase OXA-48 and the PemK/PemI TA system. Furthermore, induced expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…This is a very interesting finding, as phage vB_KpnM-VAC36 did not successfully infect strain K3320. The fundamental role played by TA systems in the inhibition of phage infection has recently been demonstrated (20,(70)(71)(72). Interestingly, an inhibitor of the TA system (protein ID: QZE51102.1) was found in the genome of the phage vB_KpnP-VAC1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a very interesting finding, as phage vB_KpnM-VAC36 did not successfully infect strain K3320. The fundamental role played by TA systems in the inhibition of phage infection has recently been demonstrated (20,(70)(71)(72). Interestingly, an inhibitor of the TA system (protein ID: QZE51102.1) was found in the genome of the phage vB_KpnP-VAC1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TEM studies revealed that fifteen phages Moreover, four (vB_KpnM-VAC13 [37], vB_KpnM-VAC25, vB_KpnM-VAC36 and vB_KpnM-VAC66 [38]) were found to be members of the family Myoviridae, which is characterized by an icosahedral capsid and a rigid, contractile tail. Finally, only two phages were identified as members of the family Podoviridae, characterized by a small, non-contractile tail (vB_KpnP-VAC1 [20] and vB_KpnP-VAC71) (Figure 1B).…”
Section: Isolation Propagation and Electron Microscopic Analysis Of P...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, for the lncL plasmid of Klebsiella pneumoniae carrying the PemIK (PemK/PemI) Type II TA System, overexpression of PemK toxin results in bacterial dormancy. 66 To bypass the toxin, phages can encode antitoxins. 67 , 68 Antitoxins can compete for the same binding site of toxins to disable their function.…”
Section: (V) Bacterial Infection Through the Abi System Leads To Fail...mentioning
confidence: 99%